Assessment of Neurodevelopmental Status and Risk Factors for Adverse Neurodevelopmental Outcome in Late Preterm Infants at 6 Months Corrected Age : An Prospective Observational Study - Hoq, Tanjina; Chowdhury, Pranab Kumar; Barua, Sanat Kumar; Hasan, Syeda Humaida; Biswas, Suman; Datta, Mitra; Ahmed, Farid Uddin (Journal of Chittagong Medical College Teachers’ Association, 2021)
Background: Late Preterm (LP) infants, previously considered low risk, have been identified to be at risk of developmental problems in infancy and early childhood. There is limited information on the outcome of these infants in low and middle income countries. This study was aimed to assess the neurodevelopmental status of LP born neonates and to determine factors associated with adverse neurodevelopmental outcome in a tertiary hospital of Chattogram, Bangladesh. Materials and methods: In this prospective observational study, 108 LP (34 to <37 completed weeks gestation at birth) infants were enrolled from the Special Care Neonatal Unit (SCANU) Chittagong Medical College Hospital (CMCH) from June 2018 to May 2019. Neurodevelopmental assessment was done by Rapid Neurodevelopmental Assessment (RNDA) at 1, 3, and 6 months of Corrected Age (CA). Results: Of the 108 enrolled children, 30 (27.8%) attended all 3 follow-up, 69 (63.9%) had incomplete follow-up, and 9 (8.3%) died. At final follow-up, out of 30 infants, 25 (83.3%) had no abnormality in all 8 domains of RNDA. Three infants (10.0%) had abnormalities in one domain and 2 (6.7%) had abnormalities in 5 domains. Gross motor abnormality was most common abnormality (13.4%), followed by speech (10.0%), and cognition (6.7%). Small for gestational age was found to be the only independent predictive factor for Neurodevelopmental Abnormality (NDA) in LP infants. Conclusion: This study demonstrates that 16.7% of the LP infants had evidence of neurodevelopmental impairment at 6 months of corrected age. SGA was an important risk factor of adverse neurodevelopmental outcome. Thus, LP infants in Bangladesh require long-term follow-up to monitor developmental outcome. JCMCTA 2021 ; 32 (2) : 70-74